THE SKIN BARRIER IN SENSITIVE SKIN SYNDROME - Filka Georgieva (Peytchinski Publishing, 2021)
Background: Sensitive Skin Syndrome (SSS) is predominantly a self-defined condition without objective pathological findings. The syndrome presents with sudden and easily provoked flushes accompanied by unpleasant sensations like itching, pain or numbness in response to stimuli that usually do not cause such sensations. The intact skin is a barrier to uncontrolled water loss, plasma components and proteins from the organism. It is therefore assumed that one of the possible explanations of itching and other unpleasant sensations in SSS should be resulting in a dysfunctional skin barrier. Purpose: was to establish is there a dysfunction of the skin barrier in SSS patients. Objective and Methods: The presented study includes 64 females self-diagnosed with SSS and 45 females self-diagnosed with NSS (non-sensitive skin). Demographic data were collected from registers of Medico-Aesthetic Center "Medea" Varna from April 2017 till April 2019. Trans epidermal Water Loss (TEWL) and Hydration (H) of the epidermis in three different areas of the body were measured as an indicator of normal skin barrier functioning. Results: No significant differences in skin barrier indicators in SS compare to NSS were found. No visible pathological changes were found in patients according to the duration of SSS. A slight correlation between abnormal levels of TEWL and H and the severity of disease was obtained. Conclusion: All the reported and analyzed results indicate that disorders of the skin barrier are slightly connected with the severity and duration of SSS. This could be one of the explanations why adding topical treatment worsen rather than improve SSS. This is the first study in our country, which aims to measure the impact of changes in skin barrier on clinical characteristics of SSS.